Sex disparities in attitudes towards intimate partner violence against women in sub-Saharan Africa: a socio-ecological analysis - Lawoko Stephen; Uthman Olalekan A; Moradi Tahereh (BMC, 2010)
Abstract Background Attitudes towards intimate partner violence against women (IPVAW) has been suggested as one of the prominent predictor of IPVAW. In this study, we take a step back from individual-level variables and examine relationship between societal-level measures and sex differences in attitudes towards IPVAW. Methods We used meta-analytic procedure to synthesize the results of most recent data sets available from Demographic and Health Survey (DHS) of 17 countries in sub-Saharan Africa conducted between 2003 and 2007. Pooled odds ratio (OR) and 95% confidence intervals (CI) were computed for all countries. Test of heterogeneity, sensitivity analysis, and meta-regression were also carried out. Results Women were twice as likely to justify wife beating than men (pooled OR = 1.97; 95% CI 1.53- 2.53) with statistically significant heterogeneity. The magnitude in sex disparities in attitudes towards IPVAW increased with increasing percentage of men practicing polygamy in each country. Furthermore, magnitude in sex disparities in attitudes towards IPVAW decreased monotonically with increasing adult male and female literacy rate, gender development index, gross domestic product and human development index. Conclusion This meta-analysis has provided evidence that women were more likely to justify IPVAW than men in sub-Saharan Africa. Our results revealed that country's socio-economic factors may be associated with sex differential in attitudes towards IPVAW.